Marital Status and Earnings Management. Issue 1 (2nd January 2017) - Hilary, Gilles; Huang, Sterling; Xu, Yanping
Abstract: In this note, we examine the effect of CEO marital status on the riskiness of financial reporting. Using multiple proxies, we find that firms headed by a single CEO display a higher degree of earnings management than those headed by a married CEO. The effect is economically significant. Our results persist in an instrumental variable regression, suggesting that our results are not driven by innate heterogeneity in preferences.